Penguatan Karakter Toleransi Melalui Kegiatan Intrakurikuler dan Ekstrakurikuler - Vina Aulia; Yadi Ruyadi; Wilodati Wilodati (Jayapangus Press, 2026)
The lack of tolerance is one of the threats to societies rich in diversity. This phenomenon still often occurs in diverse societies, including among students. Character building is one of the things that needs to be done by every educational institution, including tolerance. Every educational institution is responsible for strengthening tolerance through both intracurricular and extracurricular activities. This study aims to analyze the strengthening of tolerance through intracurricular and extracurricular activities. The approach used in this study is descriptive quantitative with data collection techniques in the form of questionnaires. Educational institutions play an important role in strengthening tolerance in students. Intracurricular and extracurricular activities have made a positive contribution to strengthening tolerance in students, both through knowledge and implementation. Character education through intracurricular and extracurricular activities can prevent the weakening of character in students, including intolerance.